Ideas of four-fermion operators in electromagnetic form factor calculations - Ji, Chueng-Ryong; Bakker, Bernard L. G.; Choi, Ho-Meoyng; Suzuki, Alfredo T. [UNESP] (American Physical Society (APS), 2013)
Four-fermion operators have been used in the past to link the quark-exchange processes in the interaction of hadrons with the effective meson-exchange amplitudes. In this paper, we apply the similar idea of a Fierz rearrangement to the self-energy and electromagnetic processes and focus on the electromagnetic form factors of the nucleon and the electron. We explain the motivation of using four-fermion operators and discuss the advantage of this method in computing electromagnetic processes. © 2013 American Physical Society.